Reactive power as an ancillary service. - Bhattacharya, K.
This paper addresses the problem of reactive power procurement by an independent system operator (ISO) in deregulated electricity markets. A reactive bid structure is proposed in the context of a reactive power market. Based on the reactive power price offers and technical constraints involved in reactive power planning, a two-tier approach is developed to determine the most beneficial reactive power contracts for the ISO. The reactive capability of a generator and therefore the opportunity costs in providing reactive power is also included in the model. Uncertainty in reactive demand and in reactive bids of participating parties is incorporated through Monte Carlo simulations and the expected reactive power procurement plan for the ISO is hence determined. The CIGRE 32-bus network, approximately representing the Swedish system, is used for the studies
Keywords: CIGRE 32-bus network; Monte Carlo simulations; Swedish power system; Ancillary service; Deregulated electricity markets; Independent system operator; Reactive bid structure; Reactive capability; Reactive demand uncertainty; Reactive power; Reactive power market; Reactive power planning; Reactive power price; Reactive power procurement; Technical constraints